Clues to the universe - Li, Christina (Quill Tree Books, an imprint of HarperCollins Publishers, 2021)
Told from their different points of view, aspiring rocket scientist Ro and introverted artist Benji become science class partners and unlikely friends, together setting out to build a rocket and search for Benji's long-lost father using clues in his favorite comic books series.